2020
DOI: 10.3390/ijerph17124390
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Life Expectancies by the Effects of Hypertension and Diabetes for the Middle Aged and Over in Taiwan

Abstract: (1) Introduction: This study aims to investigate the disparity in the healthy life expectancy of the elderly with hypertension and diabetes mellitus. (2) Materials and Methods: This study used survey data collected in five waves (1996, 1999, 2003, 2007, and 2011) of the “Taiwan Longitudinal Study on Aging” (TLSA) to estimate the life expectancy and healthy life expectancy of different age groups. The activities of daily living, the health condition of hypertension and diabetes and the survival statuses of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 13 publications
0
15
0
2
Order By: Relevance
“…The LTCs specified in the inclusion criteria and identified in the included studies were mainly self-reported. Thirteen studies reported a single condition [4][5][6]10,28,[30][31][32][33][34][35][36][37], while the remaining 17 [7][8][9][10][11][12][13][14][15][16][17][18]27,29,[38][39][40] reported the impact of more than one condition ranging from two to nine LTCs. Despite the high number of studies reporting more than one LTC,…”
Section: Overview Of Ltcs and Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…The LTCs specified in the inclusion criteria and identified in the included studies were mainly self-reported. Thirteen studies reported a single condition [4][5][6]10,28,[30][31][32][33][34][35][36][37], while the remaining 17 [7][8][9][10][11][12][13][14][15][16][17][18]27,29,[38][39][40] reported the impact of more than one condition ranging from two to nine LTCs. Despite the high number of studies reporting more than one LTC,…”
Section: Overview Of Ltcs and Outcomesmentioning
confidence: 99%
“…Nineteen studies [4,5,8,[10][11][12][13][14][15][16][17][18]27,29,31,34,36,38,41] (Table 2) examined the impact of diabetes on health expectancy. Four out of the 19 studies (representing five population samples) provided estimates of SEs or 95% CI of DFLE at age 65 and could be included in a meta-analysis.…”
Section: Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsai and Lee [ 27 ] pointed out the key factors of weight, betel nut chewing, IADL (Instrumental Activity of Daily Living), exercise, hypertension, heart disease, kidney disease, drinking, and depression conditions in diabetes mellitus of the aged. Liang et al [ 28 ] investigated the disparity in the healthy life expectancy of the elderly with hypertension and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%